Ultra-Wideband Coplanar-Fed Monopoles: A Comparative Study - Jilkova, Jana; Raida, Zbynek (Společnost pro radioelektronické inženýrství, 2008)
The paper provides an experimental comparison of four types of ultra-wideband coplanar-fed planar monopole antennas. Parameters of the open stub completed by an L-shaped monopole and the cross monopole were adopted from the literature. The forked monopole and the coplanar monopole were fabricated and measured. Monopoles were compared from the viewpoint of the impedance bandwidth, gain, directivity patterns and dimensions.
Keywords: Ultra-wideband monopole antennas; coplanar feeding; planar antennas; numerical modeling